SIMONE MARIA DE MORAES - ENGLISH VERSION - Bastos, Morgana Abranches (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Professor Simone Maria de Moraes has a bachelor’s degree in mathematics from the Pontifical Catholic University of São Paulo, a master’s degree in mathematics from the University of São Paulo, and a PhD in mathematics from the University of Campinas. The professor develops numerous researches, and some of her areas of interest are: Differential Geometry, Theory of Singularity and Topology.